1,25(OH)₂D₃ inhibits ferroptosis in nucleus pulposus cells via VDR signaling to mitigate lumbar intervertebral disc degeneration - Qiang Li; Jing Peng; Fan Ding (Scientific Reports)
Abstract Lumbar intervertebral disc degeneration (LIDD) serves as a principal contributor to low back pain, a condition that poses considerable global health and socioeconomic challenges. Recent studies have emphasized the significance of ferroptosis, an iron-dependent mechanism of programmed cell death, in the degeneration of nucleus pulposus cells (NPCs). This research examines the protective role of 1,25-dihydroxyvitamin D₃ [1,25(OH)₂D₃], the active metabolite of Vitamin D (VD), in LIDD through the modulation of ferroptosis. The results indicate that 1,25(OH)₂D₃ significantly inhibits ferroptosis in NPCs through the reduction of lipid peroxidation, restoration of glutathione levels, and enhancement of antioxidant defenses. 1,25(OH)₂D₃ exerts its effects by activating the VD receptor (VDR) signaling pathway, which regulates important ferroptosis-associated molecules, including glutathione peroxidase 4 (GPX4) and solute carrier family 7 member 11 (SLC7A11). The findings indicate the therapeutic potential of 1,25(OH)₂D₃ in alleviating LIDD, presenting a new strategy to inhibit ferroptosis and maintain intervertebral disc function.